HUBUNGAN PERHATIAN ORANG TUA DENGAN MOTIVASI BELAJAR SISWA KELAS IV SDN 16 KOTO BARU - Agus Saputra; Dhara Atika Putri; Anggela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Anggela, 2025.” The Relationship Between Parental Attention and Student Learning Motivation of Grade IV SDN 16 Koto Baru”. Thesis. Dharmasraya: Elementary School Teacher Education Study Program, Dharmas Indonesia University. This study was motivated by parental attention to student learning motivation at SDN 16 Koto Baru, causing students to be less motivated in learning. Efforts made to motivate students to learn require attention from parents and interesting learning carried out by teachers at school. This type of research is a quantitative approach research using a correlational method. The results of the study of data analysis techniques of parental attention with student learning motivation obtained a normality test value of 0.915, meaning that the value is greater than 0.05 so that the value is normally distributed, a simple linear regression test of the correlation value between variables (R) which is 0.587 obtained a coefficient of determination (R Square) of 0.345, meaning that the influence of the variable of parental attention with student learning motivation is 34.5%. Hypothesis test correlation number of 0.587 t value 3.973 with sig (P) = 0.000 significant level p <0.05 (Very significant). It can be concluded that Ho is rejected Ha is accepted, meaning the hypothesis that states that there is a relationship between parental attention and student learning motivation, the higher the parental attention, the higher the student's learning motivation. The coefficient of determination/effective contribution of R ^ 234.5% means that the research variable of parents provides an effective contribution coefficient with student learning motivation of 34.5% while 74.5% comes from other variables.